A test of the democratic peacekeeping hypothesis: Coups, democracy, and foreign military deployments. (May 2021) - Levin, Jamie; MacKay, Joseph; Jamison, Anne Spencer; Nasirzadeh, Abouzar; Sealey, Anthony
While peacekeeping's effects on receiving states have been studied at length, its effects on sending states have only begun to be explored. This article examines the effects of contributing peacekeepers abroad on democracy at home. Recent qualitative research has divergent findings: some find peacekeeping contributes to democratization among sending states, while others find peacekeeping entrenches illiberal or autocratic rule. To adjudicate, we build on recent quantitative work focused specifically on the incidence of coups. We ask whether sending peacekeepers abroad increases the risk of military intervention in politics at home. Drawing on selectorate theory, we expect the effect of peacekeeping on coup risk to vary by regime type. Peacekeeping brings with it new resources which can be distributed as private goods. In autocracies, often developing states where UN peacekeeping remuneration exceeds per-soldier costs, deployment produces a windfall for militaries. Emboldened by new resources, which can be distributed as private goods among the selectorate, and fearing the loss of them in the future, they may act to depose the incumbent regime. In contrast, peacekeeping will have little effect in developed democracies, which have high per-troop costs, comparatively large selectorates, and low ex-ante coup risk. Anocracies, which typically have growing selectorates, and may face distinctive international pressures to democratize, will likely experience reduced coup risk. We test these claims with data covering peacekeeping deployments, regime type, and coup risk since the end of the Cold War. Our findings confirm our theoretical expectations. These findings have implications both for how we understand the impact of participation in peacekeeping – particularly among those countries that contribute troops disproportionately in the post-Cold War era – and for the potential international determinants of domestic autocracy.